TEACHER’S COMMUNICATION MASTERSHIP: GROUNDWORK AND IMPLICATION TO PEDAGOGY SKILL FOR EFFECTIVE TEACHING - M. Daud Batubara; Nurbianta Nurbianta (Dinasti International Journal of Education Management And Social Science, 2020)
Basically, this research was to evaluate the learners respond about the teacher’s communication skill role in their success of academic. Hence, the goal of this research was to determine the extent of teacher’s communication skill at STAIN Mandailing Natal, North Sumatra. To ensure effective teacher treatment, effective communication skill plays role important. To this purpose the extent to which a teacher practice the communication skill in teaching and learning process. This research was performed by using survey, the researcher distributed questionnaire to collect data needed to obtain the role of communication mastership in intensify teacher's pedagogy skill. The design was quantitative descriptive research. The population consists of 494 students of Islamic Education Department major, meanwhile the sample size of 32 students at the 6th semester was randomly selected. The instrument was questionnaires as data taker tool & weighted mean. To interpret the weighted mean for each indicators, the Likert-type scale and finding of this research was average shows effective